MELATONIN IN COMPLEX TREATMENT OF GASTROESOPHAGEAL REFLUX DISEASE IN CHILDREN - O. V. Syresina; Y. A. Zhukova; T. A. Vidmanova; L. V. Korkotashvilly; S. A. Kolesov; O. A. Nefedova (Педиатрическая фармакология)
The article is devoted to gastroesophageal reflux disease (GERD) in children, which is of great medical and social significance. In spite of contemporary achievements in therapy, the diseaset is characterized by repeated relapses with complications. Hence it is very important to search for new pathogenetic schemes of esophagitis treatment. Therefore the efficacy of melatonine in complex therapy of gastroesophageal reflux disease was evaluated in 20 children. During the treatment a definitely positive dynamics was achieved: elimination of pain syndrome, absence of palpatory pain in epigastrics and pyloroduodenal region, decrease of the frequency of dyspeptic tendencies and also a significant decrease of registration of gastroesophageal reflux in control endoscopic investigation, improvement of acidforming function of the stomach as well as regulatory processes in digestion due to normalization of melatonine level were confirmed. It was scientifically proved that the use of the medicine in complex treatment of patients with GERD allows to increase efficacy of the studied therapy in 2,5 times.